BETWEEN CODE AND MOTION: GENERATIVE AND KINETIC POETRY IN FRENCH, PORTUGUESE, AND SPANISH. - Portela, Manuel (Romance Notes, 2011)
The article discusses the work of Philippe Bootz, founding member of Lecture, Art, Innovation, Recherche, Écriture (LAIRE) and theorist of programmed literature. It comments on the relationship between digital computer code and literature, addressing the materiality of the display and poetics. Other topics explored include programming poetry, patterns of specific writing processes, and automatic text generation.